Hubungan Tingkat Kecemasan dengan Tingkat Efikasi Diri Pada Atlet Renang - Kusumadewi, Isnindri Annisa; Ghozali, Dhoni Akbar; Hastami, Yunia; Wiyono, Nanang (Faculty of Sport and Health Sciences, 2021)
Anxiety might give the tremendous impact on swimming athletes such as loss of concentration and motor ability which could result in lowering athlete’s performance level in competition. Therefore, there was self efficacy as a psychological aspect which decreasing anxiety level on swimming athletes. A high self efficacy might enable athletes to face and handle the hard situations and also manage their anxiety in competition. This study aimed to determine whether there was a relationship between anxiety amd self efficacy in swimming athlete. This research was an observational study using a cross sectional approach. The subjects were 40 swimming athletes from Pyramid Swimming Club, Bogor aged 10-18 years old. The dependent variable was anxiety which measured using the Taylor Minnesota Anxiety Scale (TMAS) Questionnaire. The independent variable was self-efficacy which measured using a General Self-Efficacy (GSE) Questionnaire. Statistical analysis was performed using Product Moment Pearson test. The result showed there was correlation between anxiety and self-effcicay in swimming athletes as indicated with significance value of 0.031 and the correlation strength was low at 0.298 and the direction of correlation was negative. Based on these result it can be conclude that, there was negative correlation between anxiety and self-efficacy in swimming athletes.